Resistin Gene Expression is Downregulated in CD4+ T Helper Lymphocytes and CD14+ Monocytes in Rheumatoid Arthritis Responding to TNF‐α Inhibition. (26th September 2016) - Nagaev, I.; Andersen, M.; Olesen, M. K.; Nagaeva, O.; Wikberg, J.; Mincheva‐Nilsson, L.; Andersen, G. N.
Abstract: Rheumatoid arthritis (RA) is caused by complex interactions between immune cells and sustained by Th1 response cytokines. Resistin [resistance to insulin; (RETN)] is an inflammatory cytokine, first discovered in murine adipocytes. In man, RETN is mainly secreted by monocytes. The distinct role of RETN in the immune reaction is uncertain; however, RETN has pro‐inflammatory, pro‐fibrotic and possibly tolerogenic properties. The aim was to assess the reaction of RETN gene expression to TNF‐ α inhibition (I) in pathogenetic immune cell subsets in RA, in the context of Th1, inflammatory and regulatory cytokine gene expressions. Accordingly, we measured RETN, IFN‐ γ, TNF‐ β, IL‐1 β, TNF‐ α, TGF‐ β and IL‐10 gene expressions in CD14 + monocytes, CD4 + T helper (Th) lymphocytes (ly), CD8 + T cytotoxic (Tc) ly and CD19 + B ly in active RA before and 3 months after start of TNF‐ α I. Leucocyte subsets were separated by specific monoclonal antibody‐covered beads, RNA extracted and levels of RETN, Th1 response, inflammatory and regulatory cytokine mRNAs measured by quantitative reverse transcription‐polymerase chain reaction technique. We found that TNF‐ α I caused a significant downregulation of RETN gene expression in CD14 + monocytes and CD4 + Th ly and was unchanged in CD8 + Tc ly and CD19 + B ly. Both in active RA and during TNF‐ α I, RETN mRNA levels were significantly higher in CD14 + monocytes than in all other examined cell types. In monocytes, fold change in RETN and TGF‐ β gene expressions upon TNF‐ α I correlated significantly. Our findings indicate that RETN has pro‐inflammatory as well as proresolving roles in active RA.